Peran Guru dalam Membentuk Karakter Religius Siswa di SD Islam Al Isyroq - Wahyu Gilang Romadhon; Haikal Firmansyah; Fikri Maulana Amrullah (AJER: Advanced Journal of Education and Religion, 2025)
Education is fundamental for every individual, because with education individuals have good characteristics. Because a strong nation is a nation with character, students need to develop character that is in accordance with applicable norms, especially religious norms. Teachers have a central role in implementing character education because teachers have the most interaction with students. Character education is very suitable to be applied in the educational environment, especially religious character, because with it students can control themselves not to carry out negative actions. The aim of this research is to find out the role of teachers in shaping students' religious character. This research uses descriptive qualitative methods and data collection techniques carried out by observation, interviews and documentation. The results of this research reveal that teachers play a very important role in shaping students' religious character. Teachers act as mentors, educators, trainers, assessors. In forming students' religious character. Teachers need to get students used to carrying out religious activities, forms of activities related to religious teachings include making it a habit to invite students to recite prayers before studying and after studying, dhuha prayers, noon prayers, tahfidz al-Quran, phbi, alms and reciting Asmaul Husna.